The asymmetric security landscape; the road ahead - Manwaring, Max G. (Tiede ja ase, 2004)
Dr. Max G. Manwaring holds the General Douglas MacArthur Chair and is Professor of Military Strategy at the U.S. Anny War College. If the appropriate magic could be conjured and one could look down through the familiar artificial political lines and colours of a current world map into the twenty-first century strategic reality, one could see a complex new security arena. A deeper look into that picture would provide magical snapshots that show several types of ambiguous and asymmetric conflicts, and state failure-and their causes and consequences. It is in this general context that international organizations such as the United Nations, regional organizations such as NATO, and individual national powers such as the United States confront a succession of failing and failed states. Then, with some additional adjustments of focus, one can discern a number of issues that cannot be shown in two-dimensional space. They are briefly discussed as follows. First and importantly, one can get a better idea of the Complex Threat Situation and the Ultimate Threat-State Failure. Second, an even deeper examination of the Vision of Contemporary Wars reveals the shadows of things that have been and of those that will be on the road ahead. Third, a closer look at the familiar and troubling world map exposes some Signposts on the Road Ahead that indicate the most significant changes in the landscape. Finally, our magical microscope reveals a short list of the basic Challenges and Tasks that can help discerning civilian and military leaders negotiate the road through the asymmetric global security environment."